2011
DOI: 10.1177/0193945911407090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Unit-Level Staffing on Medication Errors and Falls in Military Hospitals

Abstract: This study examined unit-level associations of nurse staffing and workload, and the effect of the practice environment on adverse patient events. A secondary analysis was conducted of a longitudinal data set of 23 Army inpatient units from the Military Nursing Outcomes Database. Generalized Linear Mixed Modeling accommodated nested, nonparametric data. Staff category was found to be a significant predictor of medication errors and patient falls, but the relationship varied by unit type. Patient census had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…This finding held for all inpatient nursing units where LPNs were used. The effect of complexity of diagnosis and increased errors has been found in other research (Breckenridge‐Sproat, Johantgen, & Patrician, ; Hall, Doran, & Pink, ).…”
Section: Background and Literature Reviewsupporting
confidence: 67%
“…This finding held for all inpatient nursing units where LPNs were used. The effect of complexity of diagnosis and increased errors has been found in other research (Breckenridge‐Sproat, Johantgen, & Patrician, ; Hall, Doran, & Pink, ).…”
Section: Background and Literature Reviewsupporting
confidence: 67%
“…In addition, Poisson regression would be the appropriate statistical method to use, rather than linear regression, when the objective is to fit a statistical model for which the dependent variable is a rate. 32 Although Breckenridge-Sproat et al 18 initially obtained data on the number of nursing HPPDs on the unit during the shift when falls occurred, the nursing HPPD data used for their statistical analysis were ''aggregated to the month level for each unit, resulting in a total number of 833 'unit-months','' and the relationship between nursing HPPDs and fall rate was examined using these 833 data points. Thus, a direct comparison of the nurse staffing level on the shifts when falls occurred to the shifts when falls did occur was not made, which might explain why Breckenridge-Sproat et al 18 did not find a relationship between units' number of nursing care HPPDs and the fall rate.…”
Section: Discussionmentioning
confidence: 99%
“…McGillis Hall et al 17 did not observe a relationship between nurse staffing and patient falls in a descriptive correlational study of 19 teaching hospitals. BreckenridgeSproat et al, 18 Blegen and Vaughn, 19 and Blegen et al 20 did not see a relationship between nurse staffing and patient falls when analyzing unit-level data aggregated over 1-month, 1-quarter, and 1-year periods, respectively. On the other hand, Sovie and Jawad 21 analyzed data from 29 teaching hospitals summarized over a 1-year period and found that more nursing hours per patient-day (HPPDs) were associated with lower fall rates.…”
mentioning
confidence: 98%
“…[2][3][4][5][6][7][8] Other studies, however, have not supported these inverse associations. [9][10][11][12] The inconsistent findings may result from differences in study designs (eg, longitudinal vs. cross-sectional), level of measurement (eg, hospital-level vs. unit-level), analytic methods (eg, descriptive vs. multivariate analysis), data sources, and techniques used for risk adjustment of patient outcome measures. Another potential reason for the inconsistency across studies is the variation in nurse staffing measures.…”
Section: S Ince the Publication Of The Institute Of Medicine Reportmentioning
confidence: 99%